Pulse-synchronous torsional nystagmus. Issue 5 (16th July 2021) - Milenkovic, Ivan; Sycha, Thomas; Berger-Sieczkowski, Evelyn; Rommer, Paulus; Czerny, Christian; Wiest, Gerald
Abstract : Purely torsional spontaneous nystagmus almost always has a central vestibular cause. We describe a man with spontaneous pulse-synchronous torsional nystagmus in which the clockwise component corresponded to his pulse upswing, in keeping with a peripheral vestibular cause; following imaging we diagnosed left-sided superior canal dehiscence syndrome. Identifying pulse synchronicity of spontaneous nystagmus may help to distinguish central from peripheral vestibular torsional nystagmus, and is readily confirmed at the bedside using Frenzel's glasses and a pulse oximeter.